Local Embeddedness - Pickles, John (International Encyclopedia of Geography: People, the Earth, Environment and Technology, 2016)
In economic geography and economic sociology, embeddedness refers to the ways in which relational, institutional, and cultural contexts shape economic life. In contrast to the undersocialized and utilitarian assumptions of neoclassical economics, rational choice theory, and new institutional economics, theories of embeddedness focus on the ways in which markets and society are variously articulated in particular societies, organizations, and places. Embeddedness in this sense is associated first and foremost with the work of Karl Polanyi. Polanyi argued that the market generally sought to disembed itself from social regulation, while society responded by attempting to socialize and regulate (re-embed) the excesses of unregulated markets. It is also associated with the work of Granovetter in economic sociology, who cautioned against oversocializing, as well as undersocializing, the economy, in favor of a much more detailed analysis of the specific ways in which social relations structured economic practices.
Keywords: POLANYI, Karl, 1886-1964; culture; economy; embeddedness; institutions; society; undersocialized